2014
DOI: 10.4236/ojrad.2014.41017
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-Enhanced CT-Guided Core Biopsy of Retroperitoneal Masses

Abstract: Objective: To evaluate the efficacy, feasibility and safety of contrast-enhanced CT-guided core biopsy of retroperitoneal masses. Materials and Methods: Contrast-enhanced CT-guided biopsy of retroperitoneal masses was performed in 26 patients. Histopathological diagnosis was obtained and accuracy was calculated. Two blinded radiologists determined feasibility of biopsy procedures on routine CT-guidance, and compared accessibility of target lesions using contrast-enhanced and non-contrast-enhanced CT. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Patients undergoing imaging-guided biopsies in sites that have poor hemorrhage control are at a higher risk of complications [10, 11]. Multiple studies have shown that various periprocedural techniques, including smaller-gauge biopsy devices, use of closure tools, and post-biopsy tract embolization, all have the potential to decrease the rate of bleeding complications [10, 11, 12, 13, 14]. These techniques are routinely used by IR, but uncommonly by non-IR radiologists or other physicians, who are less familiar with the technique and equipment.…”
Section: Discussionmentioning
confidence: 99%
“…Patients undergoing imaging-guided biopsies in sites that have poor hemorrhage control are at a higher risk of complications [10, 11]. Multiple studies have shown that various periprocedural techniques, including smaller-gauge biopsy devices, use of closure tools, and post-biopsy tract embolization, all have the potential to decrease the rate of bleeding complications [10, 11, 12, 13, 14]. These techniques are routinely used by IR, but uncommonly by non-IR radiologists or other physicians, who are less familiar with the technique and equipment.…”
Section: Discussionmentioning
confidence: 99%